2013
DOI: 10.1128/jcm.02820-12
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Genomic Virulence Traits of a Staphylococcus epidermidis Strain Causing Native-Valve Endocarditis

Abstract: We applied real-time genome sequencing to a Staphylococcus epidermidis strain that caused native-aortic-valve endocarditis in a 26-year-old patient. The 2.5-Mb genome from strain CSUR P278 exhibited a unique sequence type among S. epidermidis strains and contained 32 genes previously considered virulence genes in this species. CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We identified eight studies for S. epidermidis [ 29 , 30 , 40 , 41 , 42 , 43 , 44 , 45 ], four for S. capitis [ 46 , 47 , 48 , 49 ], three for S. lugdunensis [ 32 , 50 , 51 ], two for S. haemolyticus [ 52 , 53 ], and one for S. caprae [ 54 ] and S. saprophyticus [ 55 ].…”
Section: Research Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified eight studies for S. epidermidis [ 29 , 30 , 40 , 41 , 42 , 43 , 44 , 45 ], four for S. capitis [ 46 , 47 , 48 , 49 ], three for S. lugdunensis [ 32 , 50 , 51 ], two for S. haemolyticus [ 52 , 53 ], and one for S. caprae [ 54 ] and S. saprophyticus [ 55 ].…”
Section: Research Methods and Resultsmentioning
confidence: 99%
“…Yet, whole-genome data can be used as a complementary tool when a putative virulence factor is identified, sometimes starting from clinical considerations. In 2013, Fournier et al provided observations of a patient with S. epidermidis endocarditis, and the authors found several clues that could explain the virulence of this strain [ 43 ]. Besides known virulence factors such as MSCRAMMs, exoenzymes, and hemolysins, the authors identified a previously unreported prophage, a new toxin/antitoxin module, and a complete icaABCD operon, which was usually not observed in non-pathogenic strains.…”
Section: Research Methods and Resultsmentioning
confidence: 99%
“…This strategy might offer rapid and exhaustive access to the virulence determinants 59 , antibiotic resistance markers 60 or genotypes 61 of unusual or difficult-to-grow bacterial strains isolated from clinical specimens. Recent examples of the use of whole-genome sequencing in clinical microbiology include the investigations of hospital outbreaks of A. baumannii, S. aureus and Clostridium difficile infections 62,63 , and the identification of the virulence determinants of a Staphylococcus epidermidis strain that was the aetiological agent of native valve endo carditis 64 . In addition, as demonstrated recently, NGS might also enable complete genome sequencing of a pathogen directly from a clinical specimen 65 .…”
Section: Sequencing Of Microbial Genomesmentioning
confidence: 99%
“…Three main strategies are used to identify virulence-factor-encoding genes in genomes [ 67 ]: first, comparison of genomes from strains or species exhibiting diverse degrees of virulence; second, identification of laterally transferred genomic islands, assuming that virulence genes are often acquired by this mechanism [ 67 ]; and, third, running the genome against databases of known virulence markers. The first approach was used in studies between Y. pestis , the causative agent of plague, and the less-virulent but closely related species Y. pseudotuberculosis [ 10 ], between a pathogenic strain of E. coli O157:H7 and a non-pathogenic laboratory strain of E. coli K-12 [ 68 ],[ 69 ], between a highly virulent Staphylococcus epidermidis causing community-acquired endocarditis and commensal strains [ 70 ], and between Klebsiella pneumoniae strains [ 71 ]. The second strategy enabled the identification of pathogenicity islands in various species [ 72 ]-[ 75 ], such as E. coli or S. aureus .…”
Section: Detection Of Virulence Factorsmentioning
confidence: 99%
“…Such a strategy enables, within a few hours, exhaustive access to the genotype [ 39 ], virulence markers and antibiotic-resistance repertoire. Real-time genomics has notably been used to investigate several nosocomial [ 70 ],[ 114 ] or community-acquired infections [ 115 ]-[ 118 ] (Table 3 ). Sherry and colleagues used PGM sequencing of four MDR E. coli strains to confirm that the nosocomial outbreak that had occurred in a neonatal unit in Melbourne, Australia, had been caused by a unique clone and to characterize the resistance genes for this outbreak strain [ 118 ].…”
Section: Real-time Genomics For the Diagnosis Of Infections Or The Inmentioning
confidence: 99%